Historical DNA of rare yellow-eared bats Vampyressa Thomas, 1900 (Chiroptera, Phyllostomidae) clarifies phylogeny and species boundaries within the genus. Issue 1 (31st December 2022) - Tavares, Valéria da C.; Gardner, Alfred L.; Mcdonough, Molly M.; Maldonado, Jesús E.; Gutiérrez, Eliécer E.; Velazco, Paúl M.; Garbino, Guilherme S. T.
Abstract : Patterns of rarity, endemism, and vulnerability are known for four species of yellow-eared bats of the genus Vampyressa : V. melissa, V. voragine, V. elisabethae, and V. sinchi, the last two described based on skull and external morphology. We extracted DNA from the holotypes of V. elisabethae and V. sinchi using strict ancient DNA protocols and sequenced the complete cytochrome- b gene of the mtDNA to investigate the phylogenetic relationships within the genus and employed species-delimitation tests to evaluate the validity of all the currently named species of Vampyressa . The resulting tree topology and our species-delimitation analyses corroborate the validity of V. elisabethae and V. voragine, but places V. sinchi in V. melissa . Based on these results and phenotypic variation, we recognize five valid species in Vampyressa and treat sinchi as a subspecies of a polytypic V. melissa ; for which we provide a rediagnosis. Our results show that V. elisabethae is as highly divergent genetically as it is morphologically, and suggest that V. thyone, one of the two species of Vampyressa known to have wide distributions, is a species complex requiring further investigation.